Mothers' income recovery after childbearing - Nikolay Angelov; Arizo Karimi (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2012)
This paper examines the time profile of the effect of fertility on female labour earnings with respect to time since birth. To address endogeneity of fertility to labour income, we use the same-sex instrument (Angrist and Evans, 1998) in a novel way on a panel data set to uncover the time profile of the fertility effect. Our OLS estimates suggest that the largest impact takes place during the child's first years of life, and then gradually diminishes over the lifecycle, with full recovery of income 15 years after birth. Our IV estimates support this finding, but suggest a faster recovery of earnings, although the estimates are now less precise. We are also able to reproduce this finding with a one-period cross-section and disaggregating the sample by years since third birth to estimate the time profile.
Keywords: J13; J22; 330; Fertility; female labour supply; same-sex siblings; instrumental variables; Fertilität; Fraueneinkommen; Zeit; Instrumentalvariablen-Schätzmethode; Schweden